PENGARUH POLA ASUH DEMOKRATIS TERHADAP KEMANDIRIAN SISWA DI MTsN 1 KOTA TANGERANG - Fathia Alida Safina; Nurmawati Nurmawati (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to determine whether there is a significant influence between democratic parenting on student independence at MTsN 1 Tangerang City. The research method used in this research is quantitative method. This study uses a sample technique taken with certain considerations, namely purposive sampling technique with consideration of the criteria for students who are parented using democratic parenting. Thus in this study an initial survey was conducted using a questionnaire questionnaire to find out students who met the research criteria category. In this study, the sample size that met the research criteria after going through the initial research stage using a questionnaire questionnaire was 57. The results showed 11 students with a high level of democratic parenting, 38 students with a moderate level of democratic parenting and 8 students with a low level of democratic parenting. The results of the level of independence show that there are 12 students with a high level of independence, 40 students with a moderate level of independence and 6 students with a low level of independence. The results of this study resulted in a value of 0.003 which based on these results shows the presence of 13.3% where if democratic parenting is carried out well, the higher the independence of students.